The Wildlife Malaria Research network (WIMANET): Meeting report on the 1st WIMANET workshop - Rafael Gutiérrez-López; Martina Ferraguti; Kasun H. Bodawatta; Carolina R.F. Chagas; Nayden Chakarov; Mélanie Duc; Tamara Emmenegger; Luz García-Longoria; Ricardo J. Lopes; Josué Martínez-de la Puente; Swen C. Renner; Diego Santiago-Alarcon; et al. (International Journal for Parasitology: Parasites and Wildlife)
The Wildlife Malaria Network (WIMANET) is a groundbreaking multinational collaboration focused on studying vector-borne haemosporidian parasites in wildlife. Unlike human malaria, wildlife malaria is found on all continents except Antarctica, with parasites being transmitted by a range of vectors. The complexity and diversity of these parasites makes it necessary to have an interdisciplinary approach to understand and mitigate their impacts. Established in 2023 within the framework of COST-Action (European Cooperation in Science and Technology), WIMANET unites researchers from diverse scientific backgrounds to tackle critical questions about wildlife malaria on a global scale. This meeting report summarises the activities and plans resulting from the 1st meeting of WIMANET's six working groups, spanning the genetic and morphological identification of parasites to understanding the drivers of host-parasite-vector associations from individual to community levels. WIMANET's collaborative efforts aim to fill the knowledge gaps and foster large-scale research initiatives transcending local and regional boundaries.